Multiplex analysis of pro-inflammatory cytokines in serum of Actinobacillus pleuropneumoniae-infected pigs. (October 2015) - Wyns, H.; Croubels, S.; Vandekerckhove, M.; Demeyere, K.; De Backer, P.; Goddeeris, B.M.; Meyer, E.
Abstract: Porcine pleuropneumonia is a severe respiratory disease caused by Actinobacillus ( A. ) pleuropneumoniae . The aim of the present study was to analyze serum samples of A. pleuropneumoniae -infected pigs for TNF-α, IL-1β and IL-6 using a cytometric bead array (CBA) 3-plex assay and additionally for IL-6 using ELISA. The CBA 3-plex assay was successfully validated for use in serum. The limits of detection varied between 0.012 and 0.333 ng/mL, and the inter- and inter-assay coefficients of variation were < 5% and < 10%, respectively. Increased levels were observed for all 3 cytokines following experimental infection with A. pleuropneumoniae . Mean peak concentrations of TNF-α and IL-6 were recorded at 12 h and at 10 h p.i., respectively. For IL-6, similar concentration-time profiles were observed with CBA and ELISA. It is proposed that this immuno-assay can be applied for the screening of immunomodulatory properties of drugs and vaccine adjuvants in infection, inflammation and vaccination. Highlights: A CBA 3-plex assay was successfully validated for use in porcine serum samples. Serum of A. pleuropneumoniae -infected pigs was analyzed for TNF-α, IL-1β and IL-6. Increased levels were observed for all 3 cytokines. Maximal concentrations of TNF-α and IL-6 were recorded at 12 h and at 10 h. A similar concentration-time profile was observed for IL-6 with CBA and ELISA.